Efforts to Improve Learning outcomes the Beautiful Theme of Togetherness Through Learning Models Discovery Learning Grade IV Elementary School - Purba, Lusi Anna; Silaban, Patri Janson; Sari H.S, Dyan Wulan; Abi, Antonius Remigius (JURNAL PAJAR (Pendidikan dan Pengajaran), 2024)
This research aims to improve student learning outcomes using the Discovery Learning learning model on the theme The Beauty of Togetherness, the sub-theme Togetherness in Diversity in class IV of Sei Beras Sekata Catholic Private Elementary School for the 2022/2023 Academic Year. This research is Classroom Action Research (PTK), the subjects in this research are 25 class IV students, consisting of 11 male students and 14 female students. The data collection techniques used are observation and tests. The results of this research indicate an increase in student learning outcomes. The results of the research in cycle I were 8 students who got a pass mark or 32%, while 17 students who did not complete it or 68% with an average score of 61.96. In Cycle II there were 22 students who met the criteria for completeness or 88%, while there were 3 students who did not complete it or 12% with an average score of 80.32. So there was an increase from cycle I compared to cycle II and it had fulfilled the specified completeness. Furthermore, teacher activity in cycle I observation obtained an average of 72% and in cycle II it increased to 92%, while student activity in the learning process in cycle I obtained an average of 60% and in cycle II it increased to 90%.